A space for discussion on the trade of the Indies: The Board of Commerce (Junta de Comercio) and the Projects for the Creation of the Companies (1682-1685) - Rodríguez García, Margarita Eva (Revista Complutense de Historia de América, 2022)
From the beginning of the 1680s, Cadiz consolidated its role at the head of the Carrera de Indias, due in part to its repeated offers of services to ease the financial needs of the Monarchy. The city´s dynamism, the support given by the Consulate to the communities of foreign merchants who sent their goods to America, was in stark contrast to the situation in Castile whose factories and commerce were in a state of decline. In 1679 the Junta de Comercio was created with the fundamental aim of reverting this situation, by incorporating many of the contemporary mercantilist ideas of the period into its functioning. However, this institution, which in principle was not geared towards transforming the rules of American trade, came to be identified as a space for creating better connections between the Castilian productive sectors and colonial trade, while at the same time pushing the interests of groups and sectors traditionally excluded from Indian commerce. This article highlights this aspect of the Junta through the analysis of three projects for the creation of commercial companies presented between 1682 and 1684, which underlined besides their economic aspects, the political character of their commercial projects that sought to show that the interests of different territories would lead to the benefit of the whole monarchy.
Keywords: Trading Companies; Mercantilism; Board of Commerce; Monarchy of Charles II; 17th Century